Diffused Religion : Beyond Secularization - Cipriani, Roberto (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This book explores the concept of diffused religion as it is found in contemporary society, resulting from a vast process of religious socialisation that continues to pervade our cultural reality. It provides a critical engagement with a framework of non-institutional religion that is based on values largely shared in society by being diffused through primary and secondary socialisation. Cipriani also contends that these very values which give form to diffused religion can also be seen in themselves as their own kind of religion. As a result, they go beyond secularisation and favour the religious continuum extending around the world of diffused religions. This work will be of great interest to scholars in the Sociology of Religion and to anyone wanting to learn more about the social aspects of religion.
Keywords: Social sciences.; Religion and sociology.; Cultural studies.; Social medicine.; elektronické knihy; electronic books